2022
DOI: 10.2486/indhealth.2021-0217
|View full text |Cite
|
Sign up to set email alerts
|

Stress and the gig economy: it's not all shifts and giggles

Abstract: Gig work is a type of contingent work which has increased markedly in recent times, and is characterised by uncertainty, unpredictability, and instability of both schedules and income earned.Gig workers are also likely to work for multiple platforms and/or employers. These work characteristics mean that performing gig work is associated with higher rates of stress than the general population 1) . However, it is not currently known which strategies gig workers use to cope with this stressincluding which strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
1
4
0
4
Order By: Relevance
“…Through the interviews we conducted, we were introduced to themes that were both expected and unexpected. Recent studies on the gig economy, for instance, echo the financial instability that was found in our study and the mental and physical health consequences of it [11,12]. The need for benefits and access to paid leave has also arisen in recent survey work [13], where these drawbacks were reported as even more critical than insufficient income.…”
Section: Discussionsupporting
confidence: 72%
“…Through the interviews we conducted, we were introduced to themes that were both expected and unexpected. Recent studies on the gig economy, for instance, echo the financial instability that was found in our study and the mental and physical health consequences of it [11,12]. The need for benefits and access to paid leave has also arisen in recent survey work [13], where these drawbacks were reported as even more critical than insufficient income.…”
Section: Discussionsupporting
confidence: 72%
“…To examine job quality, we use the framework proposed by Eurofound, 4 which defines job quality as a multidimensional concept and distinguishes seven dimensions in it: physical environment, work intensity, skills and discretion, working time quality, social environment, prospects, and earnings. They are based on positive and negative self-reported features of the job, which measure the concrete work experience and have been proven to have a causal effect—either positive or negative—on the health and well-being of workers 25 . These job quality indices are measured on a scale of 0 to 100, except for earnings, which refer only to monthly earnings.…”
Section: Methodsmentioning
confidence: 99%
“…They are based on positive and negative self-reported features of the job, which measure the concrete work experience and have been proven to have a causal effect-either positive or negative-on the health and well-being of workers. 25 These job quality indices are measured on a scale of 0 to 100, except for earnings, which refer only to monthly earnings.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, being on call has become a common mode of employment ( Glavin and Schieman, 2022 ). However, being on call often means that workers’ mobile phones cannot be turned off for 24 h, and they must be ready to work at any time, which results in irregular work hours and easily leads to potential mental health problems ( Hafeez et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%